Role of the PE/PPE Family in Host–Pathogen Interactions and Prospects for Anti-Tuberculosis Vaccine and Diagnostic Tool Design - Qian, Jianing; Chen, Run; Wang, Honghai; Zhang, Xuelian (Frontiers in Cellular and Infection Microbiology, 2020)
The pe/ppe genes are found in pathogenic, slow-growing Mycobacterium tuberculosis and other M. tuberculosis complex (MTBC) species. These genes are considered key factors in host-pathogen interactions. Although the function of most PE/PPE family proteins remains unclear, accumulating evidence suggests that this family is involved in M. tuberculosis infection. Here, we review the role of PE/PPE proteins, which are believed to be linked to the ESX system function. Further, we highlight the reported functions of PE/PPE proteins, including their roles in host cell interaction, immune response regulation, and cell fate determination during complex host-pathogen processes. Finally, we propose future directions for PE/PPE protein research and consider how the current knowledge might be applied to design more specific diagnostics and effective vaccines for global tuberculosis control.